From craftsmen to capitalists : German artisans from the Third Reich to the Federal Republic, 1939-1953 - McKitrick, Frederick L. 1994- (Monographs in German history, 2016)
"Politically adrift, alienated from Weimar society, and fearful of competition from industrial elites and the working class alike, the independent artisans of interwar Germany were a particularly receptive audience for National Socialist ideology. As Hitler consolidated power, they emerged as an important Nazi constituency, drawn by the party's rejection of both capitalism and Bolshevism. Yet, in the years after 1945, the artisan class became one of the pillars of postwar stability, thoroughly integrated into German society. From Craftsmen to Capitalists gives the first account of this astonishing transformation, exploring how skilled tradesmen recast their historical traditions and forged alliances with former antagonists to help realize German democratization and recovery; 'Among historians, German Handwerker have typically been treated only in terms of their presumed Nazi sentiments or persistent economic backwardness. This extensively researched, well-written volume shows that these artisans were neither exclusively reactionary in their politics nor cynically sacrificed by the Nazis at the altar of the war economy'...Jay Lockenour, Temple University; 'This is an impressive study that bears directly upon important scholarly debates. McKitrick's sympathy for the plight of tradespeople in a rapidly changing society is palpable, and he rightly handles their history with a due consideration of its complexity, rather than treating them as reactionary caricatures'...Perry Biddiscombe, University of Victoria"...From publisher's website